Croatia - Restructuring Public Finance to Sustain Growth and Improve Public Services : A Public Finance Review - World Bank (Washington, DC, 2012)
The year 2000 was a turning point in Croatian history, marked by closing the chapter of the war and the first phase of transition. With that, the country turned its attention to the "second transition,"the principle goal of which is to place Croatia on a path to the European Union (EU). While opening the economy to global markets through World Trade Organization (WTO) and CEFTA memberships and reestablishing cooperation with its Southeast European neighbors, the signing of the Stabilization and Association Agreement (SAA) marked the first firm milestone on Croatia's path to EU. In October 2005, Croatia opened EU accession negotiations, with the screening phase concluded a year after. Benefiting from successful economic transformation and the EU accession negotiations, growth has remained solid, and is roughly on par with the average for the European transition countries. Inflation has been modest despite higher prices for imported oil, and has been kept in check partly due to exchange rate appreciation. In fact, the central bank has intervened to prevent stronger appreciation in the face of robust capital inflows. However, the oil and commodity price increases and the aggregate demand pressures have contributed to a widening of the current account deficit in 2005-2007, despite somewhat tighter fiscal policy. Building on this foundation, the Government has an unparalleled opportunity to place Croatia on a sustainable growth path to achieve better living standards for all and to integrate into EU. To seize this opportunity, Croatia needs to sustain macroeconomic stability and continue creating a better climate for investment. In this context, key priorities for the public sector will include: reducing the size of the state and the fiscal deficit, and thereby helping to increase private sector productivity and competitiveness; and improving public sector efficiency and effectiveness. This report will suggest ways in which these twin priorities may best be addressed.